Regulators of mitochondrial complex I activity: A review of literature and evaluation in postmortem prefrontal cortex from patients with bipolar disorder. (28th February 2016) - Duong, Angela; Che, Yi; Ceylan, Deniz; Pinguelo, Arsene; Andreazza, Ana C.; Trevor Young, L.; Berk, Michael
Abstract: Phenomenologically, bipolar disorder (BD) is characterized by biphasic increases and decreases in energy. As this is a state-related phenomenon, identifying regulators responsible for this phasic dysregulation has the potential to uncover key elements in the pathophysiology of BD. Given the evidence suggesting mitochondrial complex I dysfunction in BD, we aimed to identify the main regulators of complex I in BD by reviewing the literature and using the published microarray data to examine their gene expression profiles. We also validated protein expression levels of the main complex I regulators by immunohistochemistry. Upon reviewing the literature, we found PARK-7, STAT-3, SIRT-3 and IMP-2 play an important role in regulating complex I activity. Published microarray studies however revealed no significant direction of regulation of STAT-3, SIRT-3, and IMP-2, but a trend towards downregulation of PARK-7 was observed in BD. Immunocontent of DJ-1 ( PARK-7 -encoded protein) were not elevated in post mortem prefrontal cortex from patients with BD. We also found a trend towards upregulation of DJ-1 expression with age. Our results suggest that DJ-1 is not significantly altered in BD subjects, however further studies are needed to examine DJ-1 expression levels in a cohort of older patients with BD. Highlights: PARK-7, STAT3, SIRT-3, and IMP-2 play an important role in regulating complex I activity. Published microarray data revealed trend towards downregulation of PARK-7 in patients with BD. Immunocontent of DJ-1 was not increased in post-mortem prefrontal cortex from patients with BD.